Assessment of factual measurement times for chlorophyll-a fluorescence in rubber (Hevea brasiliensis) clones - Andi Nur Cahyo; Rudi Hari Murti; Eka Tarwaca Susila Putra; Tri Rini Nuringtyas; Denis Fabre; Pascal Montoro (Society for Indonesian Biodiversity, 2021)
Abstract. Cahyo AN, Murti RH, Putra ETS, Nuringtyas TR, Fabre D, Montoro P. 2021. Assessment of factual measurement times for chlorophyll-a fluorescence in rubber (Hevea brasiliensis) clones. Biodiversitas 22: 3470-3477. Chlorophyll-a fluorescence is widely used to determine the stress tolerance levels of some plant species. Measurement of chlorophyll-a fluorescence is accurate if the duration of dark adaptation is well defined and optimal Fv/Fm (maximum quantum yield of primary photochemistry/photosynthesis) is achieved. Leaf clips are usually used to darken the leaf prior to measurement. This procedure takes time and limits the use of chlorophyll-a fluorescence parameter in high-throughput screening of genetic populations. This study aimed to determine the most suitable time for the chlorophyll-a fluorescence measurement. This study was carried out on several rubbers (Hevea brasiliensis Müll. Arg.) clones and consisted of two steps. The first step was conducting the measurements at five different times at night: at 7.30, 8.00, 8.30, 9.00, and 9.30 p.m. The second step was conducting the measurements at daytime, which consisted of two factors. The first factor was the measurement time, which was divided into two categories: 7.30 a.m. and 1.30 p.m. The second factor was the duration of dark adaptation using leaf clips, which consisted of nine levels: 0, 15, 30, 45, 60, 75, 90, 105, and 120 min. Additional treatment (measurement at 9.00 p.m. without using leaf clips to darken the leaf) was used as a control. This study revealed that a dark adaptation time of two hours after the sunset was long enough for the rubber leaves chlorophyll-a fluorescence transient to be measured without using leaf clips for the dark adaptation. If the measurement is conducted by 7.30 a.m., the clone RRIM 600, GT1, and SP 217 required 15 min of dark adaptation, whereas clone PB 260 required 60 min of dark adaptation. Furthermore, measurement of chlorophyll-a fluorescence in the afternoon is not recommended due to the potentially high microclimate fluctuation.